Primary congenital glaucoma: An iridotrabeculodysgenesis? - Ramanjit Sihota; Karthikeyan Mahalingam; Ashok Kumar Maurya; Ajay Sharma; Anand Naik Bukke; Tanuj Dada (Indian Journal of Ophthalmology, 2024)
Purpose: To analyze primary congenital glaucoma (PCG) anterior chamber and angle anomalies over 360° as possible biomarkers of severity and prognosis. Methods: A cross-sectional observational study was conducted analyzing anterior segment anomalies of PCG patients over 4 years of age who underwent trabeculectomy combined with trabeculotomy and age-matched controls using anterior segment optical coherence tomography (ASOCT), CASIA-2. Anterior iridotrabecular adhesions or anterior iris insertion was identified and quantified from the scleral spur using the iridotrabecular contact (ITC) index parameter as a surrogate. Results: There was a variable but significantly increased anterior iridotrabecular adhesion on ITC index, ITC area, corneal volume, anterior chamber volume, iris volume, anterior chamber depth, and small/absent trabecular meshwork in PCG eyes compared to control eyes. In PCG eyes, anterior iridotrabecular adhesion had a positive correlation with pre-operative central corneal thickness (CCT) (r = 0.53, P = 0.02), review iris thickness (r = 0.4, P = 0.04), and ITC area (r = 0.85, P < 0.001). Review iris thickness had a negative correlation with pre-operative vertical cup-disc ratio (r = -0.51, P = 0.008). Iris hypoplasia with fewer or absent folds, collarette, pupillary ruff, and pupillary ruff to collarette distance was significantly different from controls. Conclusion: ASOCT in PCG eyes has shown that they have variable anterior iridotrabecular tissue adhesions, anomalous tissue/membranes in the angle, and iris hypoplasia correlating with pre-operative cup-disc ratio. These features could be used as gonioscopic and clinical biomarkers to assess the severity and prognosis of the disease. The presence of abnormal iris morphology and iridotrabecular tissue anomalies in PCG suggests that it is more than just isolated trabeculodysgenesis and is probably best considered as part of the anterior segment dysgenesis spectrum.